Thermal and structural characterization of Cu-Al-Mn-X (Ti, Ni) shape memory alloys - Canbay, C. Aksu; Genc, Z. Karagoz; Sekerci, M. (Springer, 2014)
In this study, the Cu-Al-Mn-X (X = Ni, Ti) shape memory alloys at the range of 10-12 at.% of aluminum and 4-5 at.% manganese were produced by arc melting. We have investigated the effects of the alloying elements on the transformation temperatures, and the structural and the magnetic properties of the quaternary Cu-Al-Mn-X (X = Ni, Ti) shape memory alloys. The evolution of the transformation temperatures was studied by differential scanning calorimetry with different heating and cooling rates. The characteristic transformation temperatures and the thermodynamic parameters were highly sensitive to variations in the aluminum and manganese content, and it was observed that the nickel addition into the Cu-Al-Mn system decreased the transformation temperature although Ti addition caused an increase in the transformation temperatures. The effect of the nickel and the titanium on the thermodynamic parameters such as enthalpy and entropy values was investigated. The structural changes of the samples were studied by X-ray diffraction measurements and by optical microscope observations at room temperature. It is evaluated that the element Ni has been completely soluble in the matrix, and the main phase of the Cu-Al-Mn-Ni sample is martensite, and due to the low solubility of the Ti, the Cu-Al-Mn-Ti sample has precipitates, and a martensite phase at room temperature. The magnetic properties of the Cu-Al-Mn, Cu-Al-Mn-Ni and Cu-Al-Mn-Ti samples were investigated, and the effect of the nickel and the titanium on the magnetic properties was studied.
Keywords: Martensitic-Transformation; Damping Capacity; Phase-Stability; Thermodynamics; Manganese